MODEL INTERAKSI ETER MAHKOTA Bz15C5 TERHADAP KATION Zn2+ DAN Cd2+ BERDASAR PERHITUNGAN DENSITY FUNCTIONAL THEORY - , NURUL HIDAYATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The selectivity of Bz15C5 to bind Zn2+ and Cd2+ metal cations in gas and solvent phase was studied using Density Functional Theory (DFT) calculation with LANL2MB basis set. The affects of microsolvation and substituens on the selectivity of crown ether were also conducted. Modeling microsolvation in this research by addition 2H2O to cation-crown ether complexes. Selectivity of crown ether was analyzed in term of the structure parameter, energetic parameter and atomic charges. The solvent effect towards selectivity of complexes was investigated using Polarized Continuum Model (PCM). The results showed that selectivity of crown ether to Zn2+ and Cd2+ cations in gas phase were influenced by suitability of metal cations diameter with cavity size of crown ether. The selectivity of Bz15C5 to Cd2+ cations is higher than Zn2+ because diameter Cd2+ is closed to cavity size. Besides cavity size, selectivity of crown ether was also influenced by subtituent attached to the ring of benzo-crown ether. Substituents of electron donating increased the interaction energy of complex, whereas electron withdrawing decreased. The energy interaction of complex in solvent phase is lower than in gas phase as the solvent molecules weaken the cation-crown ether interaction. In a pure water solvent, the polarity of substituted Bz15C5 affected the energy interaction of complex. The high polarity of crown ether ligands decreased energy interaction of formation complexes ligand-cation. However, the lower polarity of crown ether ligands more easy to interact with cations, so the energy interaction of complexes increased.